Pengaruh Motivasi Kerja Dan Disipllin Kerja Terhadap Produktivitas Kerja - Moch. Irfan Hakim; Hadi Sunaryo; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTBased on the research carried out with the aim of analyzing the effect of work motivation and work discipline on work productivity of BAUPK UNISMA Malang staff. The population in this study were 66 staffs of BAUPK UNISMA Malang. The sampling technique used is total sampling in which this technique uses the entire total population. The method of analysis used in this research several line analyzes are analyzed by hypothesis testing using the tests of t and f. In this study, it reveals the previously thought-provoking answers, that at the same time motivational performance and work ethic affect job productivity, job motivation affects job productivity, and job management affects job productivity.                                                                              Keyword : Motivation Work, Work Discipline, Work Productivity